Muscle Attenuation Is Associated With Newly Developed Hypertension in Men of African Ancestry. Issue 5 (May 2017) - Zhao, Qian; Zmuda, Joseph M.; Kuipers, Allison L.; Bunker, Clareann H.; Patrick, Alan L.; Youk, Ada O.; Miljkovic, Iva
Abstract : Increased ectopic adipose tissue infiltration in skeletal muscle is associated with insulin resistance and diabetes mellitus. We evaluated whether change in skeletal muscle adiposity predicts subsequent development of hypertension in men of African ancestry, a population sample understudied in previous studies. In the Tobago Health Study, a prospective longitudinal study among men of African ancestry (age range 40–91 years), calf intermuscular adipose tissue, and skeletal muscle attenuation were measured with computed tomography. Hypertension was defined as a systolic blood pressure ≥140 mm Hg, or a diastolic blood pressure ≥90 mm Hg, or receiving antihypertensive medications. Logistic regression was performed with adjustment for age, insulin resistance, baseline and 6-year change in body mass index, baseline and 6-year change in waist circumference, and other potential confounding factors. Among 746 normotensive men at baseline, 321 (43%) developed hypertension during the mean 6.2 years of follow-up. Decreased skeletal muscle attenuation was associated with newly developed hypertension after adjustment for baseline and 6-year change of body mass index (odds ratio [95% confidence interval] per SD, 1.3 [1.0–1.6]) or baseline and 6-year change of waist circumference (odds ratio [95% confidence interval] per SD, 1.3 [1.0–1.6]). No association was observed between increased intermuscular adipose tissue and hypertension. Our novel findings show that decreased muscle attenuation is associated with newly developed hypertension among men of African ancestry, independent of general and central adiposity and insulin resistance. Further studies are needed to adjust for inflammation, visceral and other ectopic adipose tissue depots, and to confirm our findings in other population samples. Abstract : Supplemental Digital Content is available in the text.